Transformation Strategy of Pesantren Wali Songo Ngabar in Responding to Modern Education - Wathoni, Kharisul (EDUKASIA, 2023)
Pesantren can now play a role and compete with educational institutions in general, especially in trying to adapt to the development and progress of the times. On the other side, manypesantren can stand on equal footing with general educational institutions in terms of mastery of science and technology. It is evidently an added value because, on the one hand, it remains a center for Islamic studies by trying to maintain old traditions that are still relevant, while on the other hand, it remains inclusive of various issues of change that occur outside the pesantren. The efforts of Pesantren to gain public trust are carried out in earnest to provide satisfaction to the community as "graduate users" at Pesantren and Wali Songo Ngabar. The research method used qualitative with a case study approach. The results achieved began with formulating a strategy to increase public trust carried out by Wali Songo through several stages, namely planning, organizing, actuating and controlling, related to strategies to gain public trust. Its implementation includes strategies in managerial, economics, and leadership. The implications for increasing public trust are in the form of economic, psychological-social, and academic regulatory implications, all of which increase the existence of pesantren in the eyes of society.